2021
DOI: 10.1021/acs.jpcb.1c00036
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Molecules Alter the Energy Landscape of Small Aβ1–42 Oligomers

Abstract: Small amyloid-beta (Aβ) oligomers are believed to be key pathogenic species in Alzheimer's disease (AD). One suggested toxicity mechanism is the detergent model where oligomers remove lipid molecules from the bilayer. Senile plaques of AD patients also accumulate a ratio 1:1 of cholesterol/Aβ. What are the dominant structures of small Aβ42 oligomers with cholesterol molecules in aqueous solution? Here we answer this question by performing atomistic replica exchange molecular dynamics simulations of Aβ42 dimers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

6
2

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 70 publications
(135 reference statements)
2
18
0
Order By: Relevance
“…This phenomenon is affected by specific lipids including cholesterol, sphingomyelin, and gangliosides [717,718]: lipid types typically present in the outer leaflet of the cell membrane. Amyloid fibers at a membrane surface have thus been frequently studied using MD simulations, e.g., [719][720][721][722][723][724][725][726][727][728][729][730], however, a surprisingly small fraction of this work has been performed in the context of drug design [731,732]. Khondker et al, proposed designing drugs with a mode of action that involved modulating membrane properties to affect the aggregation of amyloid-β25-35 at the bilayer surface [229].…”
Section: Can Drugs Prevent Amyloid Formation Via the Modification Of Membrane Properties?mentioning
confidence: 99%
“…This phenomenon is affected by specific lipids including cholesterol, sphingomyelin, and gangliosides [717,718]: lipid types typically present in the outer leaflet of the cell membrane. Amyloid fibers at a membrane surface have thus been frequently studied using MD simulations, e.g., [719][720][721][722][723][724][725][726][727][728][729][730], however, a surprisingly small fraction of this work has been performed in the context of drug design [731,732]. Khondker et al, proposed designing drugs with a mode of action that involved modulating membrane properties to affect the aggregation of amyloid-β25-35 at the bilayer surface [229].…”
Section: Can Drugs Prevent Amyloid Formation Via the Modification Of Membrane Properties?mentioning
confidence: 99%
“…Furthermore, the simulations show that dimer formation on membranes with Chol inside occur almost 2X faster than on a similar membrane without Chol [ 12 ]. The effect of Chol on the free energy and conformational sampling has also been reported for Aβ dimers and trimers [ 32 ]. In addition to significant changes to the FEL, the authors also report that presence of Chol induces greater β-structure content in the dimers and trimers of the Aβ(1-42); they also report that dimer to trimer change in β-structure is also significant when Chol is present, going from 26% to 41% [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of Chol on the free energy and conformational sampling has also been reported for Aβ dimers and trimers [ 32 ]. In addition to significant changes to the FEL, the authors also report that presence of Chol induces greater β-structure content in the dimers and trimers of the Aβ(1-42); they also report that dimer to trimer change in β-structure is also significant when Chol is present, going from 26% to 41% [ 32 ]. The discrepancy in fraction of β-structure secondary structure between monomer and oligomers can be explained by data obtained by Ono et al, in which different pure oligomers of defined sizes were compared [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…30 Atomistic simulations emerge as appropriate methods for evaluating the structural changes and interactions between biomolecules. 35,36 Therefore, in this work, a fragment of NAb bind to 501Y.V2/wildtype (WT) S proteins were revealed using molecular dynamics (MD) and steered-MD (SMD) simulations. Furthermore, the obtained results indicated that 501Y.V2 complex is less stable compared with the WT one.…”
Section: Studyingmentioning
confidence: 99%